Comparison of cinefluoroscopy and M mode echocardiography for detecting aortic valve calcification. Correlation with severity of stenosis of non-rheumatic aetiology. Issue 4 (April 1984) - Dancy, M; Leech, G; Leatham, A
Abstract : The density of aortic valve calcification was estimated using cinefluoroscopy and M mode echocardiography in 86 patients with pure aortic stenosis. The results were compared with the degree of outflow obstruction measured haemodynamically. Cinefluoroscopic estimates of aortic valve calcification correlated well with the measured aortic valve gradient whereas echocardiographic results were less accurate. Echocardiography gave accurate information about the distribution of calcium within the cusps, but this was not of value in predicting the degree of obstruction. The amount of calcium in the aortic valve as assessed by simple cinefluoroscopy is a useful guide to the severity of aortic stenosis in patients in the middle and older age groups.